Relationship of the SITLESS intervention on medication use in community-dwelling older adults: an exploratory study - Viegas, Ruben; Alves da Costa, Filipa; Mendes, Romeu; Deidda, Manuela; McIntosh, Emma; Sansano-Nadal, Oriol; Magaña, Juan Carlos; Rothenbacher, Dietrich; Denkinger, Michael; Caserotti, Paolo; Tully, Mark A.; Roqué-Figuls, Marta; et al. (Frontiers in Public Health, 2023)
Background Sedentary behavior (SB) and physical activity (PA) interventions in older adults can improve health outcomes. Problems related with aging include prevalent comorbidity, multiple non-communicable diseases, complaints, and resulting polypharmacy. This manuscript examines the relationship between an intervention aiming at reducing SB on medication patterns. Method This manuscript presents a local sub-analysis of the SITLESS trial data on medication use. SITLESS was an exercise referral scheme (ERS) enhanced by self-management strategies (SMS) to reduce SB in community-dwelling older adults. We analyzed data from the ERS + SMS, ERS and usual care (UC) groups. Patient medication records were available at baseline and at the end of the intervention (4-month period) and were analyzed to explore the effect of SITLESS on medication patterns of use. Result A sample of 75 participants was analyzed, mostly older overweight women with poor body composition scores and mobility limitations. There was a significant reduction of 1.6 medicines (SD = 2.7) in the ERS group (p < 0.01), but not in the UC or ERS + SMS groups. Differences were more evident in medicines used for short periods of time. Conclusion The findings suggest that an exercise-based program enhanced by SMS to reduce SB might influence medication use for acute conditions but there is a need to further investigate effects on long-term medicine use in older adults.